Moving Towards Legitimate Participation. A Venezuelan Girl Learning English in an Iowa City Elementary School - Plata-Ramírez, José Miguel (2017)
This qualitative case study seeks to understand and describe, in depth, the different learning processes in which a nine-year old, Venezuelan girl (Victoria) engaged to reaffirm her identity as a language learner and become a legitimate member of a community of practice during the first six months in an Iowa City Elementary School. Data collection included observations in class and at home, field notes, interviews, oral and written artifacts and e-mails. Analysis was made through a constant comparison of the data to reflect on the potential categorizations of the artifacts considering mainly two theoretical constructs: “legitimate peripheral participation” (Lave & Wenger, 1991) and “collaborative relations of power” (Cummins, 1996). Results suggest that students engage more actively in activities, which are designed to construct meaning through social participation. Legitimate participation in school activities helped Victoria improve her English language ability and reaffirm her identity. The speed with which she learned English at school is mainly due to the solid community of practice she had the fortune to participate in and Mrs. Brown’s mediation. The more she interacted, the better she performed; and the better she performed, the more she interacted. This research offers alternative ways to understand Victoria’s experience as a language learner, the complexity of a second language learning process, and the fundamental role teachers need to perform to mediate in the students’ learning to reaffirm their identities. This study represents an exemplary reflection of what we, as classroom teachers, SL/foreign language teachers, should do in our classrooms if we really want to offer students real opportunities to learn the language and help them reaffirm their identity as language learners.